Analisis Kualitas Layanan Susi Air sebagai Operator Penerbangan Perintis di Luwu Utara - Fanggidae, Paulus Yulis; Kirani, Agnes Neisha; Melviana, Melviana (Ekonomis: Journal of Economics and Business, 2024)
Customer satisfaction is one of the main keys to determining the success of a business and its sustainability. Service businesses are business activities that require users to be in a "service encounter" and this requires creating an atmosphere and providing adequate supporting facilities, in addition to other variables, so that the service delivery process can be enjoyed and satisfy customers. Aviation services are a very promising business activity, especially to support human activities in general. Higher education must improve the quality of services offered, of course this must be equipped with various supporting attributes and create an atmosphere when carrying out "delivery service" in "service encounters" with a pleasant "ambiance situation" that needs to be created. In the midst of increasingly fierce competition and increasingly smart customers, educational institutions must be able to overcome current challenges by providing the best service. Increasing competition has encouraged many educational institutions to invest and develop quality services by integrating various aspects, such as human resources, equipment, technology and supporting programs to simplify the delivery process. Consumers tend to be less “loyal” and more easily switch to service providers that match their perceptions. This effort is also part of the organization's commitment to continuously improving quality.